2014
DOI: 10.1167/iovs.12-10303
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Lens Opacities in Nigeria: Results of the National Blindness and Low Vision Survey

Abstract: A fifth of Nigerian adults have some degree of lens opacity. Further studies are needed to investigate the role of ethnicity, climate variables, and other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 40 publications
(42 reference statements)
1
25
1
2
Order By: Relevance
“…The KOS completed the five-year ophthalmic survey project in 2012, accompanying the 2008–2012 KNHANES, and the present results are reported on behalf of the KOS. Since previous epidemiologic studies for cataract and cataract surgery vary considerably across regions, racial/ethnic groups, population structures, economic status, and healthcare systems ( 9 10 11 12 13 ), the results of this study are expected to provide a meaningful stepping stone for future investigations and establishing a public health plan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The KOS completed the five-year ophthalmic survey project in 2012, accompanying the 2008–2012 KNHANES, and the present results are reported on behalf of the KOS. Since previous epidemiologic studies for cataract and cataract surgery vary considerably across regions, racial/ethnic groups, population structures, economic status, and healthcare systems ( 9 10 11 12 13 ), the results of this study are expected to provide a meaningful stepping stone for future investigations and establishing a public health plan.…”
Section: Discussionmentioning
confidence: 99%
“…Without appropriate cataract surgery, the effect of cataract on vision in an aged population can be easily guessed ( 1 ). Historically, the association between sex and cataract has not been consistent, showing either no association ( 11 ) or a higher incidence in women ( 13 ). Differences in ethnicity, public health states, childbearing rates, and socioeconomic status may play a role in these various associations ( 11 , 12 , 14 15 16 17 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed that ARC occurs more common in female than male[ 3 , 37 , 38 , 39 , 40 ]. In our present study, female gender was also found as independent risk factors for cortical and nuclear cataract.…”
Section: Discussionmentioning
confidence: 99%
“…Cataracts are the result of opacity (clouding) in the crystalline lens, blocking the transmission of light that reaches the retina. According to the World Health Organization (WHO) it is the number one leading cause of reversible vision loss; although it is reversible by means of appropriate interventions, WHO estimates that, worldwide, cataracts are the cause of approximately 50% of the cases of blindness ( Mahdi et al, 2014 ; Patil et al, 2014 ). Due to the increase of life expectancy that leads to progressive expansion of the elderly population, the National Eye Institute, estimates the number of people in the U.S. with cataract will double by the 2050, from the current 24.4 million to about 50 million cases.…”
Section: Cataractsmentioning
confidence: 99%